Towards a compact all-optical terahertz-driven electron source - Xu, Hanxun; Li, Renkai; Yan, Lixin; Du, Yingchao; Tian, Qili; Huang, Wenhui; Tang, Chuanxiang (Frontiers in Physics, 2023)
In this study, we propose a physical design of a compact all-optical terahertz (THz)-driven electron source. The 300-mm accelerator beamline, powered by a Joule-level laser system, can be easily integrated into the tabletop scale. A THz-driven electron gun, a tapered dielectric-loaded cylindrical waveguide, THz-driven bunch compressors, and permanent magnetic solenoids (PMSs) have been designed and optimized. Dynamic simulations show that the electron source can deliver 19 fC electron beams at 3 MeV, with a normalized transverse emittance of 0.079 π.mm.mrad. A minimum relative energy spread of 0.04% or a minimum root-mean-square (RMS) bunch length of 6.1 fs can be achieved. Sensitivity analysis shows that the THz-driven electron source can effectively work with a laser power jitter within 1.5%. Simulation studies also reveal the potential of the designed THz-driven electron source for achieving high-quality ultrafast electron diffraction (UED). Prototype THz-driven electron guns have been fabricated and are currently under testing, and more comprehensive results will be reported in future works.